2012
DOI: 10.19030/jabr.v29i1.7556
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Reactions To Debt Initial Public Offering Announcements

Abstract: We examine the valuation effect of initial public debt offers on issuing firms common stock for the period 1970 to 2010. In contrast to findings for seasoned debt offerings, we find a statistically significant cumulative abnormal return of -0.24 percent over the three-day announcement period for the overall sample of 1,207 debt IPOs. Consistent with the prediction of the adverse selection model of Myers and Majluf (1984), the significant negative valuation effect of debt IPOs is only associated with risky issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Chang et al (2006) scrutinize stock market reaction around secured debt offerings and find a significant negative shareholder reaction. Cai and Lee (2013) confirm this result for the US stock market, performing a comprehensive study of the US bonds issues from 1970 to 2010. While they conclude in favor of a negative stock market reaction, their finding is only significant for speculative grade companies.…”
Section: Stock Market Reactionsupporting
confidence: 73%
See 1 more Smart Citation
“…Chang et al (2006) scrutinize stock market reaction around secured debt offerings and find a significant negative shareholder reaction. Cai and Lee (2013) confirm this result for the US stock market, performing a comprehensive study of the US bonds issues from 1970 to 2010. While they conclude in favor of a negative stock market reaction, their finding is only significant for speculative grade companies.…”
Section: Stock Market Reactionsupporting
confidence: 73%
“…Empirical literature does not provide a clear consensus with some papers concluding to a positive reaction (Miller and Puthenpurackal, 2005;Fungacova, Godlewski and Weill, 2015) while others show a negative reaction (Chang et al, 2006, Cai andLee, 2013) or no significant reaction (Mikkelson and Partch, 1986;Eckbo, 1986). In any case, these papers deal with Western countries.…”
Section: Introductionmentioning
confidence: 98%
“…Dann and Mikkelson (), Mikkelson and Megan Partch () and Eckbo () find a negative but insignificant reaction, Chang et al . () and Cai and Lee () found a negative and significant reaction, while Miller and Puthenpurackal (), Chang et al . () and Fungacova et al .…”
Section: Hypothesesmentioning
confidence: 91%
“…Empirically, shareholder reactions to a bond issue show no distinct pattern and seem to depend on which effect dominates. Dann and Mikkelson (1984), Mikkelson and Megan Partch (1986) and Eckbo (1986) find a negative but insignificant reaction, Chang et al (2006) and Cai and Lee (2013) found a negative and significant reaction, while Miller and Puthenpurackal (2005), Chang et al (2006) and Fungacova et al (2015) provide evidence of a positive valuation effect. We conclude from the empirical literature that no consensual finding has emerged for the stock market reaction following a bond issue.…”
Section: Stock Market Reactionmentioning
confidence: 97%
“…There's a rich diversity in findings on this matter. Positive market reaction to debenture issue announcements is emphasised by Brounen and Eichholtz (2001), Cai andLee (2013), andBayless &Chaplinsky (2014). Conversely, Dann andMikkelson (1984), Eckbo (1986), and Spiess & Affleck-Graves (1999) reported significant negative share price reactions.…”
Section: Introductionmentioning
confidence: 99%